A New Approach to Counseling Relations in Islamic Boarding Schools Based on the Ta'limul Muta'alim Book: An Emansipatory Hermeneutical Study - Fitriyah, Fifi Khoirul; Chuma, Mohamed; Sodikin, Mokhamad; Muhammad Afwan Romdloni; Asma’ul Lutfauziah (Universitas Nahdlatul Ulama Surabaya, 2022)
Living in an Islamic boarding school has its challenges, especially for students. Various studies on indigenous counseling, but no one has examined the culture of Islamic boarding schools. This study aimed to analyze and create the construct of counseling relationships in Islamic boarding schools to support a part of the indigenous counseling construction in the Islamic field. The research method used was a hermeneutic study using an emancipatory approach. Data analysis used the stages compiled by Paul Ricoeur. The primary data was a book of Ta'limul Muta'alim by Az-Zarnuji. The study results found elements of counseling relationships between counselors and students in Islamic boarding schools. It is not only counselors who have to manage attitudes in counseling relationships but also students. This finding was different from the previous concept of counseling relationships through a humanistic approach that the counselor must accept students unconditionally. On the other hand, empathy is an essential key in counseling relationships, so it aligns with the concept of humanistic counseling. The contribution of this research is to provide new insights into the form of counseling relationships in indigenous counseling at Islamic boarding schools. This finding is a series of constructions to create an indigenous counseling model and determine the counselor criteria in Islamic boarding schools. The structure is beneficial for counseling practice in Indonesia through the counselor’s role in Islamic boarding schools. Tinggal di pondok pesantren memiliki tantangan tersendiri, terutama bagi para santri. Berbagai kajian tentang konseling indigenous, namun belum ada yang meneliti tentang budaya pondok pesantren. Penelitian ini bertujuan untuk menganalisis dan membuat konstruk hubungan konseling di pondok pesantren untuk mendukung bagian dari konstruksi konseling indigenous di bidang keislaman. Metode penelitian yang digunakan adalah studi hermeneutik dengan pendekatan emansipatoris. Analisis data menggunakan tahapan yang disusun oleh Paul Ricoeur. Data primer berupa kitab Ta'limul Muta'alim karya Az-Zarnuji. Hasil penelitian menemukan unsur-unsur hubungan konseling antara konselor dan santri di pondok pesantren. Bukan hanya konselor yang harus mengelola sikap dalam hubungan konseling tetapi juga santri. Temuan ini berbeda dengan konsep sebelumnya tentang hubungan konseling melalui pendekatan humanistik bahwa konselor harus menerima santri tanpa syarat. Di sisi lain, empati merupakan kunci penting dalam hubungan konseling, sehingga sejalan dengan konsep konseling humanistik. Kontribusi penelitian ini adalah untuk memberikan wawasan baru tentang bentuk hubungan konseling dalam konseling adat di pondok pesantren. Temuan ini merupakan rangkaian konstruksi untuk membuat model konseling indigenous dan menentukan kriteria konselor di pesantren. Struktur tersebut bermanfaat bagi praktik konseling di Indonesia melalui peran konselor di pesantren.